The Relationship Between Age and Comorbidities (Type 2 Diabetes Mellitus and Hypertension) and Hearing Loss in Women Over 40 Years of Age - Simanjuntak, Saurma O S; Herwanto, H R Yusa; Lubis, Yuliani M; Zahara, Devira; Kananda, Vive; Ashar, Taufik (Jurnal Biologi Tropis, 2025)
Hearing loss is a public health problem that increases with age and can be exacerbated by comorbidities such as type 2 diabetes mellitus (DM) and hypertension. This study analyzed the relationship between age and comorbidities (DM type 2 and hypertension) on hearing loss in women over 40 years old. A cross-sectional analytical study of 34 women over 40 years old in Kotamatsum IV Village, Medan. Hearing examinations were performed using pure tone audiometry and otoacoustic emission (OAE). Statistical analysis was performed using the Chi-Square, Mann-Whitney, and Kruskal-Wallis tests. There was a significant relationship between age and the degree of hearing loss (p=0.047), with the majority of subjects aged >50 years experiencing mild deafness. However, no significant relationship was found between comorbidities of type 2 DM and/or hypertension on the degree, type of hearing loss, or OAE results (p>0.05). Age was significantly associated with the degree of hearing loss, while type 2 DM and hypertension did not show a significant relationship. Further research is needed considering disease duration and treatment adherence to further understand the contribution of comorbidities to hearing loss.